Adie’s Tonic Pupil in Systemic Sclerosis: A Rare Association - Anusha Venkataraman; Bijnya Birajita Panda; Chandrasekhar Sirka (Case Reports in Ophthalmological Medicine)
We report a rare association of Adie’s tonic pupil in a patient with systemic sclerosis who was otherwise systemically stable. This paper is an effort to unravel whether the tonic pupil and systemic sclerosis are an association by chance (which may be the case) or systemic sclerosis is the source of the tonic pupil.